GUEST EDITORIAL: Faces of Precarity: Restructuring Care-mentality in Asia - Dwivedi, Om Prakash; Malhotra, Isha (SARE: Southeast Asian Review of English, 2024)
SARE, Vol. 61, Issue 1 | 2024 Guest Editorial: “Faces of Precarity: Restructuring Care-mentality in Asia”